2022
DOI: 10.31387/oscm0490343
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Supply Chains of Sri Lankan Manufacturing Organizations: A Study on Operational Excellence Models During the COVID-19 Pandemic

Abstract: This paper presents an investigation on operational excellence (OpX) models of sustainable supply chains (SSCs) inSri Lankan manufacturing organizations during Covid-19 pandemic. This investigation consists of multiple case studies of Sri Lankan manufacturing organizations in following industries: rubber and plastic products, wearing apparels, paper and paper products. Based on a pre-existing OpX model, six Critical Success Factors (CSFs) were identified in terms of SSCs. This research was conducted as an expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…They have developed a model for supply chain efficiency ratio that can be applied by the firms to achieve efficiency. Malsinghe et al, (2022) also concentrates on operational excellence models to overcome the challenges during the pandemic. Additionally, several risk management tactics should be in place to combat the pandemic like reliable sourcing, safeguarding, partnership with major supplier, and real demand-based inventory management (Sumarliah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…They have developed a model for supply chain efficiency ratio that can be applied by the firms to achieve efficiency. Malsinghe et al, (2022) also concentrates on operational excellence models to overcome the challenges during the pandemic. Additionally, several risk management tactics should be in place to combat the pandemic like reliable sourcing, safeguarding, partnership with major supplier, and real demand-based inventory management (Sumarliah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sudusinghe and Seuring (2020) observed that the significant contribution of practising social sustainability within apparel manufacturing positively affects economic performance. Malsinghe et al (2022) presented an examination of operational excellence models of the sustainable supply chain in manufacturing firms in Sri Lanka. Subsequently, green innovation criteria in the form of economic criteria have been a vital component for sustainable supply chain management in textile manufacturing (Yang & Wang, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study added more important supply chain innovations, including timely sourcing of shipment to customers, eprocurement, identification of products and reverse logistics. Malsinghe et al (2022) suggested that sustainable operations could contribute to better outcomes.…”
Section: Recovery Strategiesmentioning
confidence: 99%